Strategic Agility and Talent Management on Employee Performance : The Mediating Role of Employee Engagement - M. Fahrul Husni (STIE Amkop Makassar, 2026)
This study aims to determine and analyze the influence of Strategic Agility and Talent Management on Employee Performance through Employee Engagement at PT. XYZ. The analytical tool used in this study is data analysis using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The population of this study was 147 employees at PT. XYZ, with the number of samples used being 147 employees. The sampling technique used saturated sampling technique . The results of the study show that: (1) Strategic Agility has a positive and significant effect on Employee Engagement ; (2) Talent Management has a positive and significant effect on Employee Engagement ; (3) Strategic Agility has a positive and significant effect on Employee Performance ; (4) Talent Management has a positive and significant effect on Employee Performance ; (5) Employee Engagement has a positive and significant effect on Employee Performance ; (6) Strategic Agility has a positive and significant effect on Employee Performance through Employee Engagement ; and (7) Talent Management has a positive and significant effect on Employee Performance through Employee Engagement .